Properties and Engineering Applications of a New Goaf Grouting Filling Material. (11th January 2022) - Feng, Xiao; Xia, Chong; Zhang, Sifeng; Li, Chuangui; Zhao, Hongkui; Wu, Jianfeng; Chen, Mengjun; Yan, Jia
Abstract : In the treatment of goafs in traffic engineering, technical problems such as those related to large-volume grouting and the precise control of material properties are often encountered. To address these issues, we developed a new composite material comprising cement-fly ash-modified sodium silicate (C-FA-MS). The setting time, fluidity, unconfined compressive strength, and microstructure were varied for different proportions of cement-sodium silicate (C-S) slurry, cement-fly ash-sodium silicate (C-FA-S) slurry, and C-FA-MS slurry, and their performances were compared and analysed. The experimental results showed that the initial setting time of the slurry was the shortest when both the original sodium silicate volume ratio (V S ) and modified sodium silicate volume ratio (V MS ) were 0.2. The final setting time of the C-S and C-FA-S slurries tended to decrease but then increased with decrease in V S, while that of the C-FA-MS slurry increased with lower V MS . The fluidity of the C-FA-S and C-FA-MS slurries decreased with decrease in V S or V MS at different fly ash admixture ratios. The consolidation compressive strength of C-S increased with decreasing V S, while that of C-FA-S showed a considerable increase only when V S decreased from 0.4 to 0.2. Meanwhile, the compressive strength of the C-FA-MS concretions first increased and then decreased with decrease in V MS . Microstructural analysis revealed that there were more cracks in the C-S agglomerate, the fly ash in the C-FA-S agglomerate reduced the relative density of the skeletal structure, and the stronger cross-linking in the C-FA-MS agglomerate improved the strength of the agglomerate. Under the condition of unit grouting volume, the cost of the C-FA-MS slurry was approximately 44.7% and 31.3% lower than that of the C-S and C-FA-S slurries, respectively. The new C-FA-MS material was applied for the treatment of the goaf in the Wu Sizhuang coal mine. Core drilling detection and audiofrequency magnetotelluric survey revealed that the goaf was sufficiently filled.